The Dynamics of Integrated Offshore Crane Operation Management of Handal Energy Bhd - Tengku Baderul Zaman, Ibni Sultan Mahmud (2024)
This study examines the factors and challenges of integrated offshore crane services in Malaysia. This is a qualitative study using in-depth interview methodology. A total of 13 informants from stakeholders were selected, which involved integrated offshore crane services, competitors, customers and government officials. Based on the literature review, the crane service faces various challenges and obstacles such maintenance, part availability, labour costs, talent recruitment, expertise and in addition to this, logistics units, finance and exchange rates are also being identified. This study has also discovered obstacles relating to the growth of the projects. Unstructured and semi-structured questions were asked of the informants who participated in these in-depth interviews. Information collected from interviews and in-depth observations was taken through mnemonic writing and analysed. The results of the study have been organized according to basic themes, organizational themes and global themes. In conclusion, this study has summarized a qualitative phenomenon about the business and its contribution to the country's economic growth. This study found that the contract, the services and maintenance, technological advancements, skilled shortages, environmental considerations, logistics and supply chain, cost management and asset management effect the integrated offshore crane business and also this study provides suggestions for future studies, implications, theoretical and practical issues for stakeholders in dealing with the services issues in Malaysia.